(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to demonstrate the role of Digital Marketing Co-Design in moderating research gaps, enhancing the transformation of the tourism industry and economic growth, and designing management design as a new approach for MSME entrepreneurs in creating added value services. The research design uses a mixed method. The convenience sample is the participants in the Digital marketing workshop for MSMEs in Toba, Samosir, and Humbanghasundutan districts in October 2022 (N=325). Quantitative data were obtained through questionnaires and processed using the AMOS SEM, while qualitative instruments were obtained through unstructured discussion. Digital Marketing Co-Design is proven not to increase Tourism Entrepreneurship Performance directly but needs to be done through Tourism Industry Transformation. Thus Digital Marketing Co-Design can answer the previous research gaps indirectly. The novelty presented by Digital Marketing Co-Design is increasingly sticking out when entrepreneurs can transform and adopt digital technology in their operational activities. Digital Marketing Co-Design is a transformative solution for improving the performance of MSMEs. Digital Marketing Co-Design is a solution for developing and enhancing Tourism Entrepreneurship Performance and strongly influences Accessible Tourism. As many as 38.15% of MSMEs are declared proficient and adaptive in using digital marketing; the rest still need further training. Digital Marketing Co-Design is a strategic tool and role model that provides consequences for stakeholder involvement in the digital era. Co-design is an innovative way and method to influence destination image differentiation, MSME profiles, and the variety of product and service offerings in tourist destinations. Training and workshops can bridge the MSME skills gap between districts. For this reason, employers, institutions, and local governments are expected to initiate the next training.